A Critical Examination of the Volitional Theory of Action - Harton Jr., Merle Carter (My University, 1976)
The volitional theory of action has recently been assailed as an outmoded account of human action, while attempts have been made to preserve the theory on grounds which side-step the traditional difficulties. Both approaches to the theory have left it without a coherent expression. This thesis is an attempt to give a coherent theoretical foundation to the theory and to effect its critical evaluation. Preceding a discussion of the theory is a historical appreciation of its tradition, and this is used as a backdrop for viewing two aspects of the theory which serve today as its paradigms. The one is an analysis of human action in terms of a volition which is considered as something which an agent performs, and the other is an analysis of human action in terms of a volition connected causally to an item of behavior, The incompatibility of these aspects is indicated, and an attempt is made to locate them within a wider theoretical structure. This is done by distinguishing between atomic actions and instrumental actions and by attributing to the theory two definitions of an individual human action which preserve these paradigms and which account for both sorts of actions. The final segment of the thesis is concerned with a critical dismissal of the theory. The stock arguments against the theory are first defeated, end it is then argued that one aspect of the theory fails to account for forbearances and that the other aspect does not provide an adequate account of atomic actions.
Keywords: volitional theory of action, outmoded account, human action, performs, analysis, behaviour